Indigenous science disaster risk reduction: A conceptual model integrated learning in Indonesian elementary schools - Putu Eka Suarmika; Nuris Hidayat; Mufarrahatus Syarifah (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2025)
As a vulnerable group, elementary school students need to be directly involved in disaster risk reduction through learning at school. Local wisdom in disaster risk reduction, bridging the gap with modern risk reduction. This study aims to produce a model in science learning by using local wisdom learning resources for disaster risk reduction. The data analysed were articles focused on local wisdom in Indonesia using qualitative meta-analysis. The data source is articles published in indexed journals by Scopus, with the criteria of selected articles (research or review) related to local wisdom in disaster risk reduction in Indonesia. The research findings are that (1) indigenous communities have original cognitive thinking skills for responding to disasters and (2) a conceptual science learning model based on indigenous knowledge to train students' responses to disasters. Disaster risk reduction by directly involving vulnerable groups (elementary school students) provides benefits: students will learn about disasters, understand actions before a disaster occurs, understand the process of saving themselves when a disaster occurs, and be directly involved in emergency response.